Specimens of ancient architecture exhibited in the porch and belfry of St. Alphage, London Wall - Unknown (Tufts Archival Research Center, 2008)
Formerly the Chapel of the Priory of Elsynge Spital. With a plan of the Sion College and the vicinity. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 1.